Persebaran Penduduk yang Tidak Memiliki Dokumen Kependudukan di Indonesia - Irdam Ahmad (Forum Geografi, 2011)
There are two main problems of population administration system in Indonesia. Firstly, population data is not well managed and overlapped among many government institutions. Secondly, many people do not possess population documents because they did not report any vital events that have been occurred in their family, such as birth, death, move in and move out. These problems then cause list of election voters (DPT) in 2009 general election (Pemilu) are not valid. This study would like to know geographic maps of people that do not possess population documents by province. In addition, this study also search factors affecting people that do not possess paper official identities, using logistic regression. The results show that out of six independent variables used in this study; age and education of head of household, distance to village office, village status (urban/rural), household income and number of household members, only distance to village office which is significant in influence people do not possess population documents.